2020
DOI: 10.1177/0972063420935540
|View full text |Cite
|
Sign up to set email alerts
|

Personal Protective Equipment: Challenges and Strategies to Combat COVID-19 in India: A Narrative Review

Abstract: The current outbreak of the coronavirus disease (COVID-19) has become a pandemic. All COVID-19-affected countries in the world are implementing containment interventions and trying their best to fight against the disease to halt the further spread of the infection and to reduce mortality. The public health workforce and healthcare staff in clinical settings are playing a crucial role in the early detection of cases, contact tracing and treatment of patients. The availability of personal protective equipment (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 7 publications
(7 reference statements)
0
37
0
2
Order By: Relevance
“…To conserve PPE for those on the frontlines ghting the coronavirus and to keep patients home, the ADA recommended on March 16, 2020, that dental o ces should restrict their practice to only emergency cases 12 . Even in our study majority of students are afraid to work without PPE kits even though India has managed the condition very well and there is no shortage of PPE kits in India 11 .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…To conserve PPE for those on the frontlines ghting the coronavirus and to keep patients home, the ADA recommended on March 16, 2020, that dental o ces should restrict their practice to only emergency cases 12 . Even in our study majority of students are afraid to work without PPE kits even though India has managed the condition very well and there is no shortage of PPE kits in India 11 .…”
Section: Discussionmentioning
confidence: 55%
“…Researches have shown that the lack of PPE has affected the morale of healthcare workers and other frontline warriors in ghting the coronavirus disease 11 . To conserve PPE for those on the frontlines ghting the coronavirus and to keep patients home, the ADA recommended on March 16, 2020, that dental o ces should restrict their practice to only emergency cases 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Personal Protective Equipments (PPE) [3,13,28] For all the cases, the PPE used were in accordance with the guidelines issued by the Ministry of Health and Family Welfare, Directorate General of Health Sciences (Emergency Medical Relief).…”
Section: Anaesthesia [4]mentioning
confidence: 99%
“…Recommendations for an Ideal Use of [6,28] -Hazmat suit or proper full sleeve impermeable disposable gown with visor and foot cover over OT scrubs (we have personally used both and found them to be equally effective) -N 95/ffp2 non valved mask -Reusable half face respirators are found to be most effective to deal with fogging uses, especially in long surgeries [23] -Surgical goggles -Face shield; however face shield is non compliant during use of microscope, when seeing through eyepiece. This can be overcome by visualizing the monitor or by use video-endoscopes -Double non powdered surgical gloves -Proper donning and doffing of PPE and ensuring the proper execution of the sterilization chain [3].…”
Section: Anaesthesia [4]mentioning
confidence: 99%
“…At the same time, steady offshoring of PPE to other countries has left the U.S. vulnerable to supply chain disruptions (38). Countries like Spain and India also suffered severe PPE shortages that placed frontline healthcare workers at risk (39). To adequately protect healthcare providers, we must address key vulnerabilities in our PPE supply chain and current practices.…”
Section: Future Directionsmentioning
confidence: 99%